2021
DOI: 10.3390/diagnostics11050857
|View full text |Cite
|
Sign up to set email alerts
|

Whole Body Low Dose Computed Tomography (WBLDCT) Can Be Comparable to Whole-Body Magnetic Resonance Imaging (WBMRI) in the Assessment of Multiple Myeloma

Abstract: Aim of the study is to compare the agreement between whole-body low-dose computed tomography (WBLDCT) and magnetic resonance imaging (WBMRI) in the evaluation of bone marrow involvement in patients with multiple myeloma (MM). Patients with biopsy-proven MM, who underwent both WBLDCT and WBMRI were retrospectively enrolled. After identifying the presence of focal bone involvement (focal infiltration pattern), the whole skeleton was divided into five anatomic districts (skull, spine, sternum and ribs, pelvis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…A recently published prospective comparison between radiography and CT reported that more new lesions and progressive disease were found using CT at follow-up every 6 or 12 months during a four-year period (31). CT has also been reported to perform at a similar level to whole-body magnetic resonance imaging in term of focal involvement, staging, distribution, and number of lesions (32).…”
Section: Discussionmentioning
confidence: 99%
“…A recently published prospective comparison between radiography and CT reported that more new lesions and progressive disease were found using CT at follow-up every 6 or 12 months during a four-year period (31). CT has also been reported to perform at a similar level to whole-body magnetic resonance imaging in term of focal involvement, staging, distribution, and number of lesions (32).…”
Section: Discussionmentioning
confidence: 99%